PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN MEMBER D’OKSIGEN CLASIK FITNES DI KOTA PADANG - Mada Saputra (Jurnal Ecogen, 2018)
Sports is an activity carried out by humans to need to be healthy and fresh, because nowadays there are many developing companies nowadays, growth of service companies engaged in sports such as fitness centers. To develop the service company, it is necessary to conduct external activities in providing the best service to its customers. And build a good corporate image in the community. The purpose of this study was to study whether the quality of service and image of the company opposed the satisfaction of members D 'Clasik Okigen Fitness City of Padang, the sample taken was 110 members of D' Okigen Clasik Fitness City of Padang using Slovin method. The research method used is a quantitative research type. The results of the study showed that the service quality and company image towards member satisfaction. Persial Company image is not significantly affected member satisfaction, while service quality emphasizes significance to member satisfaction. The company must improve the quality of services provided to members so that members continue to survive to carry out sports activities in the Clasik Fitnes Documents of the City of Padang, and also improve the company's image through marketing communications and appropriate advertising strategies to improve the company's image to the members. Keyword: Service Quality, Image, Custumer satisfaction